TANTANGAN PENDIDIKAN KEWARGANEGARAAN PADA REVOLUSI 4.0 - S, Laurensius Arliman (Ensiklopedia Sosial Review, 2020)
Today there are more and more challenges of civic education in education, from elementary to tertiary education. This happens because education is increasingly developing in accordance with the development of pressology. Of course, this matter no longer recognizes national boundaries based on time and space. Technology today can help people meet from any country. For this reason, this article wants to see how the development of civic education in the revolutionary era 4.0 and the future challenges related to civic education in the revolutionary era 4.0. The research method used in this article is a quantitative educational method, supported by comparative materials from books and journal articles. The results show, First, the development of citizenship education in the revolutionary era 4.0 follows the times and technology, so that more flexible rules are needed and in accordance with the needs of citizens of the Republic of Indonesia. Second, the future challenge related to civic education in the revolutionary era 4.0 is to introduce what are the rights and obligations of citizens, so that citizenship education is mandatory to be taught at any level of education in Indonesia.